(untitled) (Quinto Sol, 2013)
This article analyzes the formation and operation of the Pampas ranches, based on taking them as a mainly agricultural-livestock production unit oriented to the market - although this does not exclude that part of their production destined for self-consumption - characterized by private ownership of land, a relatively fixed number of permanent workers and temporary workers. This complex economic and social unit is defined by the set of social relationships that are created from the different productive sectors and the different forms of work employed.